Peran Strategi Digital, Citra Destinasi, Ulasan Wisatawan terhadap Niat Berkunjung Kembali di Sangeh Monkey Forest - Ida Ayu Gde Meila Satyawati Manuaba; Anak Agung Istri Agung Maheswari; Ni Putu Nina Eka Lestari; Putu Purnama Dewi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study examines the influence of digital promotion, destination image, and visitor reviews on revisit intention to Sangeh Monkey Forest Bali, a natural-cultural attraction increasingly exposed through social media yet lacking optimal digital engagement. Using a quantitative approach, data were collected from 130 respondents who had visited the destination and accessed online information through platforms such as TikTok, Instagram, and Google Review. The analysis was conducted using Partial Least Squares to measure the predictive relationship among variables. The findings reveal that digital promotion and destination image do not significantly influence revisit intention, while visitor reviews demonstrate a positive and significant effect, indicating that social validation plays a more dominant role than promotional messages or perceived image. These results highlight the importance of strengthening authentic visitor experiences and managing online reviews as strategic digital assets. The study provides practical implications for destination managers in improving content strategies and enhancing service quality to support revisit behavior.